2079. The Relation Between Panel Reactive Antibody Assay and Cytomegalovirus Reactivation in Seropositive Solid Organ Transplantation Recipients. (26th November 2018) - Kwon, Da Eun; Lee, Kyoung Hwa; La, Yeonju; Yoo, Seul Gi; Han, Sang Hoon; Song, Young Goo; Lee, Jae Geun; Huh, Ku Ha; Kim, Myoung Soo; Choi, Jin Sub; Kim, Soon Il; Kim, Yu Seun
Abstract: Background: Cytomegalovirus (CMV) can lead to severe morbidities and mortalities including pneumonia in particular as well as graft dysfunction through indirect immunomodulation in solid-organ transplantation recipients. High degree of HLA mismatch is a well-known risk factor of post-transplant (Tx) CMV reactivation. Recent laboratory advances for evaluating HLA mismatch can measure existence of donor-specific antibodies for single HLA allele; however, there was little evidence whether single panel reactive Ab (PRA) assay could predict CMV reactivation in SOT recipients. Methods: We retrospectively analyzed pre-Tx HLA mismatch tests in total 300 of SOT recipients. All of them were CMV seropositive in donor and recipients and received regular blood CMV VL monitoring during ≥6 months after SOT. Lung ( N = 83) and heart ( N = 76) recipients received universal prophylaxis for 3 months, and kidney ( N = 63) and liver ( N = 78) received pre-emptive CMV therapy. The single PRA test for HLA class I/II was performed by bead-based immunoassay. The percentage of PRA was calculated by following formula: (the number of positive bead reaction/the number of beads in the assay) × 100. We categorized HLA-Ab specificity into two groups according to median fluorescent intensity (MFI) of bead; (1) strong with ≥10, 000 of MFI, (2) not strong with <10, 000. The calculated PRA was obtained from the frequency of HLA alleles in normal Korean population according to formula from U.S. Organ Procurement and Transplantation Network. Results: The reactivator with ever ≥500 IU/mL of CMV had significantly higher positive percentage of HLA Class I screening test compared than nonreactivator (33.8% vs. 11.6%, P = 0.004) but not class II ( P = 0.085). The PRA and cPRA values only for HLA class I were significantly lower in nonreactivator (PRA, 0 [0–0] % vs. 0 [0–15] %, P = 0.005; cPRA, 0.5 [0–15.5] % vs. 4.5 [0–41.5] %, P = 0.030), but not class II (PRA, P = 0.393, cPRA, P = 0.446). The percentage of strong MFI group for class I in nonreactivator was significantly lower than those in reactivator (7.1% vs. 28.8%, P = 0.028), but not class II (11.6% vs. 15.8%, P = 0.512). The maximal levels of CMV VL did not have any significant correlation to MFI values of Class I nor II. Conclusion: Seropositive SOT recipients with strong PRA or cPRA values for HLA Class I in pre-Tx single PRA test had higher risk of CMV replication. Disclosures: All authors: No reported disclosures.